Clinical Utility of a Legionella pneumophila Urinary Antigen Test in a Large University Teaching Hospital - Michel Dionne; Todd Hatchette; Kevin Forward (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the clinical utility of diagnosing Legionella pneumonia by urinary antigen testing (LPUAT) in a low prevalence centre.